Dissociable temporal effects of bupropion on behavioural measures of emotional and reward processing in depression - Walsh, A; Browning, M; Drevets, W; Furey, M; Harmer, C (Royal Society, 2018)
Background: Antidepressants remediate negative biases in emotional processing early in treatment, prior to mood improvement. However, the effects on reward processing potentially relevant to the treatment of anhedonia are less clear. Here we investigate the early and sustained effects of the dopamine and noradrenaline reuptake inhibitor bupropion on behavioural measures of emotional and reward processing in currently depressed individuals. Methods: 46 currently depressed patients and 42 healthy controls participated in a repeated measures study, during which open-label bupropion was administered to only the patient group over a 6 week period without a placebo group. All participants completed the Emotional Test Battery and a probabilistic instrumental learning task at week 0, week 2 and week 6. Results: Currently depressed patients displayed negative biases in emotional processing and blunted response bias for high-probability wins compared to the healthy controls at baseline. Bupropion was found to reduce the negative biases in emotional processing early in treatment, including a significant decrease in the percentage misclassification of other face emotions as sad and the number of negative self-referent words falsely recalled between baseline and week 2. Conversely, bupropion was found to initially further reduce the response bias for high-probability wins between baseline and week 2. This effect reversed with 6 weeks bupropion treatment and reward processing was normalised compared to the healthy controls. Conclusions: Early in treatment, bupropion acts to reduce negative biases in emotional processing but exacerbates impaired reward processing. The beneficial actions of bupropion on reward processing then occur later in treatment. Such dissociation in the temporal effects of bupropion on emotional and reward processing has implications for the treatment of the different symptom domains of negative affect and anhedonia in depression.